2010
DOI: 10.1016/s0924-9338(10)71706-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of physical health in patients with schizophrenia: practical recommendations

Abstract: Improved physical health care is a pressing need for patients with schizophrenia. It can be achieved by means of a multidisciplinary team led by the psychiatrist. Key priorities should include: selection of antipsychotic therapy with a low risk of weight gain and metabolic adverse effects; routine assessment, recording and longitudinal tracking of key physical health parameters, ideally by electronic spreadsheets; and intervention to control CVD risk following the same principles as for the general population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 30 publications
(34 reference statements)
1
31
0
1
Order By: Relevance
“…According to the non-modifiable risk factors, all of the studies identified concur on the inclusion of a comprehensive personal and family medical history [2,7,[16][17][18][19][20][21]. It should include the personal and family history with regard to cardiovascular problems, comorbid conditions, diabetes, high-risk behaviors for viral illnesses, hypertension, obesity, oncological problems, substance use and smoking.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the non-modifiable risk factors, all of the studies identified concur on the inclusion of a comprehensive personal and family medical history [2,7,[16][17][18][19][20][21]. It should include the personal and family history with regard to cardiovascular problems, comorbid conditions, diabetes, high-risk behaviors for viral illnesses, hypertension, obesity, oncological problems, substance use and smoking.…”
Section: Resultsmentioning
confidence: 99%
“…If patients are under treatment with antipsychotics, it is important to take into account the patients' history of epilepsy, response to previous treatment and side effects experienced, as well as their compliance history and preferences. Bearing in mind that antipsychotics are the commonest cause of hyperprolactinemia in people with severe mental illness [19] a personal or family history of conditions associated with it (i.e. osteoporosis, breast and prostate cancer) should be also monitored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an outpatient setting, which represents the context of the typical EPI program (35), patients will be seen separately by their primary care provider for issues of general health, which may include cardiometabolic side effects related to medications. However, this can create a disconnection between the primary health care provider and the patient’s psychiatrist, and result in less thorough or frequent metabolic screening (36, 37). …”
Section: Programs To Improve Cardiometabolic Healthmentioning
confidence: 99%
“…Increased awareness by psychiatrists of the metabolic effects of psychotropic medication along with improved information to carers of people affected by severe mental illness in respect to appropriate medical care (De Hert et al 2010). Better co-ordination of a range of specialist services such as occupational therapists, pharmacists and dieticians in respect to the medical health care of people affected by severe mental illness may also be useful (Heald et al 2010).…”
Section: Wwwintechopencommentioning
confidence: 99%